ANALISIS ORGANOLEPTIK DAN KANDUNGAN PROKSIMAT PADA PUDING COKLAT DENGAN PENAMBAHAN BLACK CHIA (Salvia hispanica L.) - Indis, Nadhifah Al; Helilusiatiningsih, Nunuk; Haliza, Nadiyah Nur (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
Chia seeds is a plant of the Salvia genre which is round, flat, and oval in shape. Chia seed has 3 color of variants, they were black, white, and grayish,. In this study we used black chia was mixed with Nutrijel chocolate pudding. Black chia was chosen because it has a higher protein content than other chia seed color. There were 6 variations in this study, they were PC 0, PC 1, PC 2, PC 3, PC 4, and PC 5, each of the varians has been analyzed of organoleptic and proximate. Based on the results of this study, Nutrijel chocolate pudding with the addition of black chia from varian PC 0 until PC 5 was acceptable and liked by the panelists. The color has an average value of 4.4; the taste was 3.7; fragrance was 4.4; and texture was 3.9. And the results of the proximate analysis, we known that Nutrijel chocolate pudding with the addition of black chia has a good moisture content 63-73%; ash content was 3.44-3.55%; crude fiber content was 1.62-3.16%; crude protein content was 10.09-11.70%; and crude fat content was 1.07-4.40%. The mass of black chia more adding in to the chocolate pudding, has increased the nutritional contained (fiber, protein, and fat).